Five Questions for Residency Leadership in the Time of COVID-19: Reflections of Chief Medical Residents From an Internal Medicine Program. (August 2020) - Rakowsky, Shana; Flashner, Bess M.; Doolin, Jim; Reese, Zachary; Shpilsky, Jason; Yang, Shu; Smith, C. Christopher; Graham, Kelly
Abstract : The COVID-19 pandemic has drastically affected the traditional methods residency programs use to train their residents. Chief residents serve a unique role as part of the residency leadership to foster the education and development of the residents. Given the rapid shift in demands on physicians in the face of the pandemic, the responsibilities of the chief residents have also shifted to help prepare the residents to meet these demands as frontline providers. There is not a precedent for how residency programs respond to this crisis while maintaining their primary role to develop and train physicians. The authors have identified 5 questions chief residents can ask to guide their program's response to the demands of COVID-19 during this uncertain time in health care.